2021
DOI: 10.3389/fonc.2021.750315
|View full text |Cite
|
Sign up to set email alerts
|

KDM4 Involvement in Breast Cancer and Possible Therapeutic Approaches

Abstract: Breast cancer (BC) is the second leading cause of cancer death in women, although recent scientific and technological achievements have led to significant improvements in progression-free disease and overall survival of patients. Genetic mutations and epigenetic modifications play a critical role in deregulating gene expression, leading to uncontrolled cell proliferation and cancer progression. Aberrant histone modifications are one of the most frequent epigenetic mechanisms occurring in cancer. In particular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 112 publications
0
20
0
Order By: Relevance
“…In support of that, LSD1 is overexpressed in haematologic malignancies and its inhibition induced differentiation of AML cells through the downregulation of the chromatin protein GSE1 33 . Similarly, the oncogenic role of JMJD2 in AML, hepatocellular, breast cancer and colorectal cancer was also reported 34,35 . Nonetheless, the demethylase activity of JMJD2 was shown to be essential for the long‐term maintenance of normal haematopoiesis 36 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In support of that, LSD1 is overexpressed in haematologic malignancies and its inhibition induced differentiation of AML cells through the downregulation of the chromatin protein GSE1 33 . Similarly, the oncogenic role of JMJD2 in AML, hepatocellular, breast cancer and colorectal cancer was also reported 34,35 . Nonetheless, the demethylase activity of JMJD2 was shown to be essential for the long‐term maintenance of normal haematopoiesis 36 .…”
Section: Discussionmentioning
confidence: 84%
“… 33 Similarly, the oncogenic role of JMJD2 in AML, hepatocellular, breast cancer and colorectal cancer was also reported. 34 , 35 Nonetheless, the demethylase activity of JMJD2 was shown to be essential for the long‐term maintenance of normal haematopoiesis. 36 On the contrary, the impact of JARID1 activation on the antitumor effect of DMC and curcumin is not clear because of the oncogenic and tumour suppressive functions of JARID1 proteins, which are contingent on the protein isoform (JARID1A, JARID1B, JARID1C, JARID1D) and cell context.…”
Section: Discussionmentioning
confidence: 99%
“…Since SUMOylation is required for chromatin binding and consequently demethylase activity of KDM4A, rescuing overexpression of KDM4A-K471R mimics the knockdown phenotype ( 25 ). In addition to the viral effect, KDM4A has also been recognized as an oncogene that is highly expressed in various human cancers ( 40 , 41 ) and inhibits apoptosis ( 42 44 ). Therefore, we hypothesize that induction of KSHV reactivation in KDM4A knockdown BCBL-1 cells or cells expressing a SUMO-deficient mutant of KDM4A may lead to incomplete viral lytic replication and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Many cellular experiments revealed that a decreased level of H3K9me3 was associated with the overexpression of oncogenes; interestingly, some of these oncogenes were regulated by ER [ 19 , 25 , 27 , 29 ]. These findings supported our result that the low level of H3K9me3 was associated with a poor prognosis and this association was significant only in ER-positive (particularly ER-high positive) patients but not in ER-negative patients.…”
Section: Discussionmentioning
confidence: 99%